A categoria Personalidade na teoria da classificação de Ranganathan: discussões epistemológicas a partir e além de Aristóteles - Barros, Stella Mello e (2022)
It proposes to investigate the application of Ranganathan's concept Personality in classification theory considering Aristotelian categorical heritage and the concept of information. The object of study is the concept of Personality's ineffability in the works Prolegomena to Library Classification, Philosophy of Library Classification and Colon Classification. The aim is to investigate the links between Ranganathan's Personality and Aristotle's Substance categories in the thematic treatment of information from the perspective of the pragmatic-linguistic information turn. The hypotheses are: based on the links between the categories, these point to the fundamental relationship (:) of faceted classification theory with the greco-latin concept of information; it is possible to understand Personality from the epistemological stream of transcendental pragmatics based on the limit of concepts in Wittgenstein's language games. The collection and analysis used methods are systematic literature review and socioterminology, which had as its documentary product the presentation of the links between Aristotle and Ranganathan in the light of socioterminological theory. The corpora aim to isolate the concept of category in aphorisms of Aristotle and Ranganathan from the selection criteria definition or application of categories. The analysis and discussion seek to relate the applications of Personality in categorization with the limit of the Wittgensteinian concept based on greco-latin information philology. We discuss: the silencing of memory in colonial gestures stemming out of the perpetuation of the choice by western lines of thought to fundamentalize knowledge organization systems; the problematizations about the standard model of information and knowledge structuralization based on Aristotelian logic; the appropriation of the foundations of information philosophy in the historical-epistemological consolidation of classification theory; the ethical-epistemic unfoldings of the intersection of Aristotelian-Ranganathian categorization with epistemological-critical-philological issues of knowledge organization in the pragmatics of Ranganathian-Wittgensteinian informational studies; the dynamics between the informo and informis of information in the doctrine of thought of the Hindu tradition that epistemologically grounds the structuring of information and knowledge in the Colon Classification; a model of knowledge representation based on pragmatic-philological contributions to the question of semantic mutation based on the dynamics, alterity and multiplicity of the meanings of information in the systematic-colonized engendering of the epistemological opening in which occurs the incessant translation of the universe of knowledge in the social environment identified as ballast in the difference of the relationship pattern between the facets of subject in the varying formal configurations of documentary objects in knowledge production, perception and uses. Ranganathan's categorical method for object analysis refers to the variant configurations of objects in their distinctive colonized articulation in documents from the definition and relationship between facets (informis): with each other in a syntax (μορφή and τύπος); with the universe of knowledge on the bookshelves (platonic ἰδέα); with the particular user and his subjectivity (informis) and with society (platonic είδος).